Biodiesel production using supercritical alcohols with a non-edible vegetable oil in a batch reactor - Valle, Pedro (2010)
In the present work, the transesterification of non-edible oil with methanol and ethanol is studied. The reactor phase transitions are directly observed in a double windowed cylindrical reactor and the conversion to fatty esters is measured. The optimization of the process conditions was carried out based on a statistical design of experiments where the key process variables were studied over different ranges to obtain a reliable model for the efficiency of the reaction as a function of reaction time, temperature, pressure and alcohol to oil molar ratio. From direct observations and the modeling of the phase behavior, a better understanding of the supercritical alcohol transesterification process is obtained as well as the confirmation of the phase equilibrium predictions based on the GCA-EOS model.